PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MATERI PESAWAT SEDERHANA MELALUI METODE GROUP INVESTIGATION DENGAN BANTUAN MEDIA NYATA PADA SISWA KELAS V SEMESTER II SDN V ARJASA TAHUN PELAJARAN 2013/2014 - Amalia Risqi Puspitaningtyas (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
This research is a classroom action research that aims to improve student learning outcomes by applying Group Investigation method with real media aid on science subjects with teaching material“Simple Aircraft” for grade V students, semester II in SDN V Arjasa, academic year 2013/2014. Grade V students are consist of 9 people; there were 4 male students and 5 female students. The instruments used in this research are syllabus, RPP, and Student Worksheet. The data required forthis research obtained through interview process with grade V teacher, the topic was about student's learning process. It got to know how to invite students to be active and creative during the learning process in the classroom. The data was also obtained through the observation of application of Group Investigation method and the formative test for the subjects of Science “Simple Aircraft”. The other supporting data were field notes as well as photos of the activities. The Classroom Action Research was in 2 cycles. Cycle I consists of the stage of problem identification, planning, action, observation, and reflection. Cycle II consists of stages of planning, action, observation, and reflection. The result of the research showed that students’ outcome has increased and fulfill the minimum completeness criteria and classically completed.